1993
DOI: 10.1002/1097-0142(19930701)72:1<173::aid-cncr2820720132>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Is there an altered steroid profile in patients with endometrial carcinoma?

Abstract: Background. Besides the well‐known association between endometrial carcinoma (EC) and unopposed estrogen, androgens also may play a role in this respect; however, previous studies on endogenous estrogens and androgens in patients with EC and control subjects have yielded mostly divergent results, probably because of the use of poorly defined control groups. Methods. Circulating steroid and pituitary hormones and sex hormone–binding globulin were measured in patients with EC and matched control groups of either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Carcinogenesis hormonal mechanisms may be operating in cancer in addition to, or along with, the potential AC excess during 6 h of 15,000 ppm CE daily exposure. The presence of uterine carcinomas and the associated presence of many ovarian metastasized uterine cancers both suggest the possibility of adrenal-promoted cancer mechanism occurred in FM that has been already reported in humans (Mollerstrom, et al, 1993;Lucas, 1974). Only FM were positive in the NTP bioassay, and only FM showed hyperkinetic stereotypic running (stress) in their cages but only during exposure and two other independent studies exhibited the same type of hyperkinesis of recursive running in their cages (Griesemer and Eustis, 1994;Pottenger, et al, 1993;US EPA, 2008).…”
Section: Metastasismentioning
confidence: 74%
“…Carcinogenesis hormonal mechanisms may be operating in cancer in addition to, or along with, the potential AC excess during 6 h of 15,000 ppm CE daily exposure. The presence of uterine carcinomas and the associated presence of many ovarian metastasized uterine cancers both suggest the possibility of adrenal-promoted cancer mechanism occurred in FM that has been already reported in humans (Mollerstrom, et al, 1993;Lucas, 1974). Only FM were positive in the NTP bioassay, and only FM showed hyperkinetic stereotypic running (stress) in their cages but only during exposure and two other independent studies exhibited the same type of hyperkinesis of recursive running in their cages (Griesemer and Eustis, 1994;Pottenger, et al, 1993;US EPA, 2008).…”
Section: Metastasismentioning
confidence: 74%
“…Few prospective studies have shown no statistical association between the levels of testosterone and endometrial cancer in premenopausal women 16 whereas positive association between testosterone levels and endometrial cancer risk was observed in post menopausal women in many studies. 16,17 Many case control studies have shown that endometrial cancer risk is also increased in both pre and postmenopausal women with elevated plasma levels of androstenedione 18,19 and testosterone [20] and few did not show the association. 21,22 Androgens do not appear to have any direct stimulatory effect on endometrial cell proliferation and the results from in vitro studies suggest a reduction in proliferation rates.…”
Section: Resultsmentioning
confidence: 99%
“…This is because the level of sex-hormone-binding globulin is decreased in obese postmenopausal women 16 30–36. It is worth mentioning that although all postmenopausal women are capable of converting androgens to oestrogens under ‘physiological’ conditions,37 only those that have a high efficiency in doing so are at risk of developing endometrial cancer38 39; indeed, extrafollicular oestrogen concentrations are significantly higher in women with endometrial carcinomas relative to healthy controls 22 26 34. It is possible that some of the conversion occurs in the endometrium, through endometrial aromatase cytochrome P450, thus increasing oestrogen concentrations at the endometrial level 21 40…”
Section: Pathogenetic Mechanism In Endometrial Carcinomas At Menopausmentioning
confidence: 99%